2018
DOI: 10.37080/nmj.6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Profile in Infertile Women

Abstract: Introduction: Infertility is defined as inability to conceive after one year of regular unprotected intercourse. Thyroid disorders can lead to infertility arising from different pathophysiological mechanisms. The aim of this study is to determine the prevalence and type of thyroid disorder in infertile women and to compare the prevalence of thyroid disorder in primary and secondary infertility. Methods: A hospital-based descriptive cross-sectional study conducted in the Department of Obstetrics and Gynec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 8 publications
(13 reference statements)
2
4
0
Order By: Relevance
“…In the present study the mean (±SD) age of the participants was 27.7 (±4.2) years which was similar to other studies. 3,8,10 The mean age was significantly high in secondary infertility compared to primary infertility which can be expected due to its selection criteria and was comparable with other study. 11 Among the study population majority were having primary infertility (72.3%) than secondary infertility (27.7%), finding in common with other studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the present study the mean (±SD) age of the participants was 27.7 (±4.2) years which was similar to other studies. 3,8,10 The mean age was significantly high in secondary infertility compared to primary infertility which can be expected due to its selection criteria and was comparable with other study. 11 Among the study population majority were having primary infertility (72.3%) than secondary infertility (27.7%), finding in common with other studies.…”
Section: Discussionsupporting
confidence: 85%
“…11 The prevalence of thyroid disorder among infertile women varies from 4.6% to 25.6% in different studies and in the current study it was 18.4%. 3,4,8,10 Hypothyroidism was the most common thyroid disorder (13.6%) the prevalence of which was similar to study conducted by sharma et al (17%). 14 However other studies have showed higher 6,7,9,10 as well as low prevalence3.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…3 There are limited articles related to aetiological factors of infertility published from Nepal and Dhulikhel Hospital (DH). [4][5][6][7][8][9][10][11][12] As there are adequate numbers of infertility cases being managed in DH, this descriptive cross-sectional…”
Section: Introductionmentioning
confidence: 99%